PROCESSO DE ENFERMAGEM DIRECIONADO ÀS GESTANTES INTERNADAS EM UNIDADE PSIQUIÁTRICA: CRIAÇÃO DE PROCEDIMENTO OPERACIONAL PADRÃO - Stochero, Helena Moro (2022)
Introduction: Although pregnancy is characterized as a normal physiological process, this period may be accompanied by anxiety, depression, mood disorder, among other mental disorders. Therefore, comprehensive care planning for pregnant women to enable quality care is paramount. Technological instruments that guide nursing professionals in the care of pregnant women who are hospitalized in psychiatric centers can provide great support. Objectives: To qualify the Nursing Process, through standard procedures, in order to systematically organize nursing care for pregnant women who have been hospitalized in Psychiatric Centers. Know the perception of the nursing team in relation to the systematization of nursing care for pregnant women hospitalized in a Psychiatric Center, and To describe the process of building a standard operating procedure, which includes the components of the nursing process, with a view to systematizing and guiding nursing care for pregnant women hospitalized in Psychiatric Units. Methodology: The methodology was conducted based on the Convergent Care Research framework, with a view to enabling a circular and complementary movement of data generation and, at the same time, of intervention with best care practices in the scenario, in this case, in a psychiatric hospital center. Data collection took place between August and December 2021, through a semi-structured interview with seven nurses, sixteen nursing technicians and two nursing assistants who work in a Psychosocial Care Center within a University Hospital in the South of Brazil. For data organization and analysis, the three dimensions proposed by PCA were considered: Dimension I – Sociodemographic profile of professionals dimension; Dimension II – Professional dimension; Dimension III – Autonomy dimension. Results: Data were organized and analyzed and resulted in two thematic categories, namely: Technical, generic and impersonal care; and From impersonality to uniqueness of nursing care. The systematization of nursing care for pregnant women hospitalized in a Psychiatric Center, in the perception of the nursing team, are translated into movements that involves techniques, routines and protocols. Ensuring unique nursing care for pregnant women, especially for those hospitalized in psychiatric centers, means providing them existential meaning and leal care, from a muldimensional and multidisciplinar perspective, in order to ensure the comprehensiveness and continuity of health care. Final considerations: Nursing care for pregnant women, while in psychiatric hospitalization, demands professional qualification, interactive and specialized dialogic technologies, in addition to the promotion of a singular and multidimensional care. In this perspective, a standard operating procedure constitutes an important resource to guide and singularize the care for pregnant women hospitalized in psychiatric units. Product and its practical applicability: To describe the process to the creation and implementation of a Standard Procedures as a management and care instrument to guide the systematization and guiding of nursing care for pregnant women hospitalized in psychiatric hospitals.